Turismo na Bacia do Pacífico - Trigo, Luiz Gonzaga Godoi (1993)
"Pacific Rim" was a term used by geologistis to describe the "Ring of Fire" (the chain of volcanoes and earthquake faults) which encircles the Pacific Ocean. Now it has become a term used to describe a circle which encompasses Southeast Asia, Northeast Asia, Australasia and the South Pacific, New Zealand and America's West Coast. ln this paper, the analisis will be focused just in the East Coast of Asia, including the economical aspects of the area and its relationship with the tourism industry.